Glyphosate-resistant hairy fleabane competition in RR® soybean - Diecson Ruy Orsolin da Silva (Bragantia, 2014)
Weed competition in the soybean causes changes in morphological and physiological characteristics that reduce the competitive ability of the crop. The objective of this study was to determine the control periods and coexistence of glyphosate-resistant hairy fleabane and its interference in morphological and photosynthetic variables and RR soybean yield. A field experiment was conducted during the 2011/2012 growing season, the treatments consisted of weed interference and weed free periods of the glyphosate-resistant hairy fleabane with soybean (BRS Estância RR). The periods were 0, 7, 14, 21, 28, 35, 42 and 154 days after the soybean emergence. The results sugested no differences between the control periods for the variables evaluated. The increase interference period of the weed reduced growth, development and the photosynthetic variables in the soybean. There are positive correlations between morphological and photosynthetic variables of soybean during the weed interference. The period before the glyphosate-resistant hairy fleabane interference in the soybean crop is 24 days for plants established before the crop sowing.